Mechanics and Model-Based Control of Smart Materials and Structures - Irschik, Hans; Krommer, Michael; Watanabe, Kazumi; Furukawa, Toshio (Springer Vienna : Imprint: Springer, 2010)
Mechanics and model-based control are both rapidly expanding scientific fields and fundamental disciplines of mechatronics, sharing demanding mathematical and system-theoretic formulations and methods. The papers in this volume deal with smart materials, which allow the design and implementation of new types of actuator/sensor fields and networks. Main topics treated are fundamental studies on laminated, composite and functionally graded materials, thermal and piezoelectric actuation, active and passive damping, as well as vibrations and waves in smart structures. The book is based on the 1st Japanese-Austrian Workshop which took place in Linz in Fall 2008.